Investigating The Effect of Aerobic Interval Training with Selenium Nanoparticles on the Content of IL-6, TNF-α and IL-4 cytokines in spleen tissue of Mice with Breast Cancer - Soodabeh Chekachak; Mahdieh Molanouri Shamsi; Sara Soudi (Fasa University of Medical Sciences, 2018)
Background & Objective: Cytokines are molecules that are related to immunologic responses. Considering the antioxidant and immunologic effects of selenium nanoparticles and aerobic exercise training, the aim of this study was to examine the effects of aerobic exercise training and supplementation with selenium nanoparticles on protein content of Interleukin-4, Interleukin-6 and tumor necrosis factor Alpha in spleen tissue in mice with breast cancer. Material and Methods: 64 Balb/c mice were randomly divided into 8 groups including Control-Health, Control-Tumor, Training-Healthy, Training-Tumor, Selenium nanoparticles-Health, Selenium nanoparticles-Tumor, Selenium nanoparticles-Training-Health and Selenium nanoparticles-Training-Tumor. Animals in different groups passed 6 weeks aerobic interval training and supplementation with selenium nanoparticles before and after cancer induction. At the end of the sixth week, cytokines protein levels in spleen tissue were measured by ELISA method. Results: Based on the current study results exercise training and selenium nanoparticles caused significant decrease in tumor volume (P<0.05). Also, results showed that cancer induced a significant decrease in cytokines levels in tumor tissue (P<0.05). But concurrent using selenium nanoparticles and aerobic interval training induced increase in tumor necrosis factor Alpha levels in spleen tissue (P<0.05). Conclusion: It seems that aerobic exercise training and selenium nanoparticles supplementation could have an effective role in the activation of immune system and decreasing in tumor volume, with increasing in tumor necrosis factor Alpha as a T helper 1 cytokine.